'The dreadful done': Henry James's style of abstraction. Issue 6 (3rd June 2021) - Scott, Rebekah
ABSTRACT: Since the 1990s, when the late novels of Henry James became a touchstone for the ethical turn in literary criticism, ethical critics of different persuasions, such as Martha Nussbaum and J. Hillis Miller, homed in on certain complex terms and ambiguous avowals in James's prose in their efforts to hold him up as an 'exemplary' writer, committed to 'ethical' values such as particularity and singularity. In doing so, these critics overlooked the prospect that at this point in his career James was testing a new sort of literary abstractionism. Like painterly abstraction, literary abstraction makes room for the material and the particular at the same time as it denies them. To illustrate this, I examine a cluster of Jamesian keywords – 'do/doing/done' – from The Golden Bowl (1904) and elsewhere, to dispute the view that James systematically shuns abstraction. Instead, I propose that abstraction – depending for its effect on absorption, entanglement, and bewilderment – be read not as a withdrawal from life into 'the vague', cerebral, imaginary, or purely aesthetic realm, but a move to create deep involvements between characters and between readers and texts, and as such should be regarded as a central motivation of James's evasive late style.